Experimental evaluation of RBD palm olein as lubricant in cold metal forming by Plane strain extrusion - S., Syahrullail (2007)
The evaluations of refined, bleached and deodorised (RBD) palm olein as lubricant in cold metal forming by plane strain extrusion were investigated. Billet material was pure aluminum (JIS-A1050). Then, a series of experiments were carried out by applying paraffinic mineral oil and RBD palm olein as test lubricant at 30ºC and 15ºC. The whole experimental and analytical results were compared mutually. Extrusion load and surface roughness of billet were measured after each extrusion experiment. Relative velocity and effective strain were calculated by using visioplasticity method. The result show that the RBD palm olein has lower extrusion load compared to Paraffinic mineral oil. It is confirmed that the lubrication performance of RBD palm olein is as effective as Paraffinic mineral oil in its ability to reduce frictional constraint in a cold metal forming.